Pengaruh Motivasi Kerja dan Kepuasan Kerja terhadap Kinerja Guru SMP X Kota Cimahi - Adli Alnazhari; Dian Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine and analyze the influence of work motivation and job satisfaction on teacher performance at SMP X, Cimahi City, both partially and simultaneously. The research method used was quantitative with a descriptive and associative approach. Data were obtained from questionnaires distributed to 36 civil servant teachers as respondents, as well as secondary data in the form of teacher performance assessments, tardiness, and absence. Data analysis was performed using multiple linear regression with the help of SPSS version 25.0, accompanied by classical assumption tests, t-tests, F-tests, and coefficients of determination. The results showed that work motivation and job satisfaction had a positive and significant effect on teacher performance, both partially and simultaneously. Work motivation had a more dominant influence than job satisfaction. The coefficient of determination (R²) of 0.506 indicates that 50.6% of the variation in teacher performance can be explained by work motivation and job satisfaction, while the remainder is influenced by other factors outside the study. In conclusion, improving work motivation and job satisfaction is crucial for improving teacher performance at SMP X, Cimahi City. Keywords: Work Motivation, Job Satisfaction, Teacher Performance,Education